Brand Communities for Fast Moving Consumer Goods An Empirical Study of Members$1 (BBehavior and the Economic Relevance for the Marketer /s - Meister, Sandra; SpringerLink (Online service) (Wiesbaden : Gabler Verlag, 2012)
Do brand communities really work for FMCG? Can brand-community members be characterized by specific behavioral attributes? Are there significant differences between members and those simply visiting the brand-community site? In her study Sandra Meister derives a set of behavioral attributes relevant for brand-community members. By means of significance test and structural equation model, she examines the behavioral profile of brand-community members and compares the results with non-members. Additionally, she investigates the impact of the behavioral attributes on the brand performance: purchase intention, recommendation, and price tolerance.
Keywords: Economics; Marketing; Economics/Management Science; Marketing